Use of string test and stool specimens to diagnose pulmonary tuberculosis() - DiNardo, Andrew R. (Int J Infect Dis, 2015)
BACKGROUND: The Xpert MTB/RIF (MTB/RIF) test has advanced the field of tuberculosis (TB) diagnostics; however, depending on age and HIV status, 10–85% of individuals with presumed pulmonary TB (PTB) are unable to produce sputum. METHODS: The feasibility of using MTB/RIF and culture on stool and string test specimens from 13 adult patients with presumed PTB was studied. RESULTS: The string test was well tolerated with a median Wong Baker Faces score of 2. The string test had 100% sensitivity and specificity by MTB/RIF and 87.5% sensitivity and 100% specificity by culture. In stool, Mycobacterium tuberculosis DNA was detected in all cases of culture-confirmed PTB. CONCLUSION: The string test and stool provide diagnostic specimens that warrant further investigation.